Reliable change and minimum clinically important difference (MCID) of the Repeatable Battery for the Assessment of Neuropsychology Status (RBANS) in a heterogeneous dementia sample: Support for reliable change methods but not the MCID. Issue 3 (4th May 2019) - O'Connell, Megan E.; Gould, Benjamin; Ursenbach, Jake; Enright, Joe; Morgan, Debra G.
ABSTRACT: We compare reliable change scores and recently published anchor-based cutoffs for minimum clinically important difference (MCID) for the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) in a sample of patients diagnosed with various forms of dementia. For memory clinic patients with dementia evaluated twice over a one-year interval ( N  = 53), observed retest RBANS index scores were compared with predicted retest index scores based on regression formulae developed from cognitively healthy older adults. Patient RBANS change scores were also compared to suggested MCID anchors. Patients with dementia demonstrated a reliable decline on most RBANS indices, with evidence that the Visuospatial/Constructional and Language Indices might be less sensitive to decline over time. Although there was consistency between MCID and reliable changes in this sample, there was a substantial proportion where the MCID was exceeded, with no reliable change. We attempted to create MCIDs from the Clinical Dementia Rating Sum of Box scores for RBANS reliable change scores, but failed to find significant associations. Overall, the findings support use of the regression based reliable change approach, but we caution use of the MCID approach for the RBANS.